Decision-making institutions and voters' preferences for fiscal policies - Sergio Galletta (ETH Zurich, KOF Swiss Economic Institute, 2018)
This paper examines the effect of local political decision-making institutions (i.e., direct democracy vs. representative democracy) on citizens' preferences toward public spending. Exogenous variation in institutions comes from a regression discontinuity design, which exploits a discrete change in the probability that a municipality has representative democracy based on a legally stipulated population threshold in the Swiss canton (state) of Vaud. Fiscal policy preferences by municipality are measured by vote shares on Swiss national referendums and initiatives that, if approved, would have increased public spending. Relative to direct democracy, representative democracy reduces vote shares in favor of spending by around 5 percentage points. The effect is not due to sorting on other observables or to feedback from changes in local policies. These findings demonstrate the importance of preferences as a channel through which political decision-making institutions can affect public policies.
Keywords: D7; H7; 330; Voter preferences; decision-making institutions; Switzerland; direct democracy